Anelastic Convective Entities. Part II: Adjustment Processes and Convective Cold Top - Kuo, Yi-Hung; Neelin, J. David (Journal of the atmospheric sciences, 2025)
Seeking a family of models filling the hierarchy between steady plumes and cloud-resolving simulations, Part I of this study presented a formulation termed anelastic convective entities (ACEs). The solution includes pressure-mediated nonlocal effects in both vertical and horizontal and thus yields time-dependent simulations of convective updrafts, downdrafts, and other aspects of convection even for a single column interacting with a fixed environment through dynamically determined inflow and outflow. Here, we show how a straightforward iteration of that formulation can capture interactions among entities in a variety of choices for the geometry of the interactions. Using an oceanic sounding to contrast with land cases in Part I, we first illustrate that a single ACE can exhibit ongoing time-dependent evolution depending, e.g., on choices in the parameterized turbulence. For a case in which a single ACE with a fixed environment would yield a near-steady deep-convective state, we examine the adjustment process in a multi-ACE prototype for adjustment within a climate model grid cell. This embedded ACE configuration exhibits time-dependent stratiform cloud expansion through convective outflow modified by dynamic feedbacks. The gridscale adjustment process not only includes traditional warming by large-scale descent but also captures the spread of the convective cold top. The formulation also illustrates the possibility of multihour time lag before the transition to deep convection and remote initiation by small vertical velocities in the gridcell environment. Comparing 1-, 2-, 4-, and 8-ACE instances suggests promise as a potential convective-parameterization class between traditional and superparameterization, while providing a sandbox to aid understanding of convective and adjustment processes.